2011
DOI: 10.1128/jvi.05505-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Poxvirus Orthologues of the Vaccinia Virus E3 Protein: Modulation of Protein Kinase R Activity, Cytokine Responses, and Virus Pathogenicity

Abstract: Poxviruses are important human and animal pathogens that have evolved elaborate strategies for antagonizing host innate and adaptive immunity. The E3 protein of vaccinia virus, the prototypic member of the orthopoxviruses, functions as an inhibitor of innate immune signaling and is essential for vaccinia virus replication in vivo and in many human cell culture systems. However, the function of orthologues of E3 expressed by poxviruses of other genera with different host specificity remains largely unknown. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…The dsRNA binding activity of vaccinia E3 protein was examined mostly using the synthetic dsRNA analog poly(I·C) (24,25). In our laboratory, the specificity of the E3 protein binding to poly(I·C)-coated agarose beads has been demonstrated previously (18). In this study, the poly(I·C) bead pulldown assay was used to examine the dsRNA binding of vaccinia E3 mutant proteins.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The dsRNA binding activity of vaccinia E3 protein was examined mostly using the synthetic dsRNA analog poly(I·C) (24,25). In our laboratory, the specificity of the E3 protein binding to poly(I·C)-coated agarose beads has been demonstrated previously (18). In this study, the poly(I·C) bead pulldown assay was used to examine the dsRNA binding of vaccinia E3 mutant proteins.…”
Section: Resultsmentioning
confidence: 86%
“…Previously, it has been reported that PKR is an important regulator of apoptosis induced by the vaccinia E3L deletion mutant (18,27,28). Here, induction of the apoptotic markers cleaved poly(ADP-ribose) polymerase (PARP) and cleaved caspase-7 was examined by Western blotting.…”
Section: Suppression Of Pkr Activation By E3 Mutants Pkr Plays a Majmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, this mutated sequence has reverted to the original sequence twice on independent branches of the tree and in viruses isolated from widely separated geographic regions. M029 has been shown to function similarly to VACV E3, binding double-stranded RNA, inhibiting protein kinase R (PKR) activation, and inhibiting IFN-␤, tumor necrosis factor alpha (TNF-␣), and interleukin-6 (IL-6) expression (45); it is a critical virulence factor in rabbit infections but also has a second function of binding RNA helicase A (RHA; DHX9), which promotes virus replication in some cell lines, so it has been described as a dual-function virulence and host range factor (46). The amino acid sequence from the related leporipoxvirus RFV is conserved from amino acid 1 to 8 and is identical to that from MYXV from amino acid 20 to 55 but is poorly conserved between residues 9 and 19; this region is also divergent in the Californian MSW strain of MYXV (47).…”
Section: Pathways To Attenuation and Virulence In Australian Isolatesmentioning
confidence: 99%
“…As previous studies revealed that PKR has evolved under selection by viral inhibitors (Elde et al 2009;Rothenburg et al 2009) and that various poxvirus E3L proteins differ in their ability to inhibit human PKR (Myskiw et al 2011), we focused our studies on variola virus E3L and its natural target human PKR. Our selection of variola E3L was also spurred by the critical biodefense importance of variola virus.…”
Section: Introductionmentioning
confidence: 99%